2016
DOI: 10.1159/000447970
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2L Receptor Is Required for Visual Discrimination and Reversal Learning

Abstract: The corticostriatothalamic circuit regulates learning behaviors via dopamine neurotransmission. D2 long (D2L) receptors are an isoform of dopamine D2 receptors (D2Rs) and may act mainly at postsynaptic sites. It is well known that D2Rs influence high brain functions, but the roles of individual D2R isoforms are still unclear. To assess the influence of D2L receptors in visual discrimination learning, we performed visual discrimination and reversal tasks with D2L knockout mice using a touchscreen operant system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…As noted above, lower availability, levels and/or functionality of striatal dopaminergic D2 receptors have been consistently linked to impulsive behavioral phenotypes in laboratory rodents and human or nonhuman primates ( Kruzich and Grandy, 2004 ; Kruzich et al, 2006 ; Dalley et al, 2007 ; Boulougouris et al, 2009 ; De Steno and Schmauss, 2009 ; Buckholtz et al, 2010 ; Groman et al, 2011 ; Laughlin et al, 2011 ; Morita et al, 2016 ). D2 receptors are located within multiple cellular compartments within the striatum, including postsynaptic medium spiny neurons that project to the pallidum, as well as on dopamine-releasing terminals where they regulate dopamine synthesis and release ( Jentsch and Roth, 2000 ).…”
Section: Discussionmentioning
confidence: 91%
“…As noted above, lower availability, levels and/or functionality of striatal dopaminergic D2 receptors have been consistently linked to impulsive behavioral phenotypes in laboratory rodents and human or nonhuman primates ( Kruzich and Grandy, 2004 ; Kruzich et al, 2006 ; Dalley et al, 2007 ; Boulougouris et al, 2009 ; De Steno and Schmauss, 2009 ; Buckholtz et al, 2010 ; Groman et al, 2011 ; Laughlin et al, 2011 ; Morita et al, 2016 ). D2 receptors are located within multiple cellular compartments within the striatum, including postsynaptic medium spiny neurons that project to the pallidum, as well as on dopamine-releasing terminals where they regulate dopamine synthesis and release ( Jentsch and Roth, 2000 ).…”
Section: Discussionmentioning
confidence: 91%
“…Our findings suggest therefore that interactive effects between trait anxiety and cocaine exposure were somehow responsible for the inability of HE rats to exploit reward value during the reversal session. Reversal learning has been widely shown to depend on monoaminergic mechanisms in the OFC and striatum [75][76][77][78][79][80] with substantial evidence implicating D2 receptors in the striatal indirect pathway [81][82][83][84][85]. However, rather than decreasing DRD2 expression in the striatum, as predicted from prior positron emission tomography imaging studies in humans and other rats, [86][87][88], striatal DRD2 expression increased significantly in the DMS after 8 days of abstinence from cocaine in LE and HE rats.…”
Section: Discussionmentioning
confidence: 82%
“…Morita et al 49 reported impaired VD learning in dopamine D 2 long receptor-deficient mice. Disc1 has been shown to associate with dopamine D 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A disruption in this circuitry and/or the dopaminergic system in Disc1 Δ2‐3/Δ2‐3 mice may impair VD learning. Morita et al reported impaired VD learning in dopamine D 2 long receptor‐deficient mice. Disc1 has been shown to associate with dopamine D 2 receptors .…”
Section: Discussionmentioning
confidence: 99%